The Impact of Learning English as a Foreign Language Through Games, Dances, and Songs on the Development of Social Skills in Preschool Students (2024)
The purpose of this research is to analyse how the application of games, dances, and songs in teaching English influences the development of students' social skills. Through a qualitative approach, we analysed students' experiences and perceptions when participating in group activities that integrate musical and rhythmic movement strategies, highlighting their role in identity construction. The results reveal that these activities not only foster inclusion and appreciation of diversity in a heterogeneous learning environment but also significantly improve students' emotional and social expression and regulation. The games, dances, and visual materials used in the classes help students recognise and manage their emotions, as well as those of their peers, promoting greater emotional intelligence and developing social skills such as taking turns, sharing, helping, listening, and verbally expressing feelings. In addition, the research highlights the importance of collaborative activities in forming social skills. Students develop essential skills such as cooperation, group work, and respect for others' perspectives, crucial aspects for their personal and academic development as preschool students. Finally, the positive impact on communication skills is highlighted. Interaction in English through music and singing allows students to practice and improve their vocabulary and develop oral and listening skills, such as speaking and listening. This increases their confidence in communication and facilitates the formation of effective social relationships, which is essential for establishing social relationships.